Polycythemia Vera with Myelofibrosis and Myeloid Metaplasia: Acute Hepatic Failure Following Splenectomy. Issue 5 (31st January 2016) - McBrine, Paula A.; Miller, Aaron; Zimelman, Abraham P.; Koff, Raymond S.
Abstract : Myelofibrosis with myeloid metaplasia developed during the course of polycythemia vera in a middle-aged man. Severe megakaryocytopenia and thrombocytopenia were early features of this illness and were unresponsive to splenectomy. After splenectomy, hepatic enlargement and acute hepatic failure developed. Extensive extramedullar hematopoiesis dilating hepatic sinusoids and compressing liver cells was the major pathologic finding in the liver. The mechanism of hepatic failure in this disorder is uncertain.